Carregamento estático e dinâmico e sua relação com tensão, deformação e fluxos no solo - Brandt, André Anibal (2009)
The increased land use for food production is causing problems related to soil compaction in the different systems of land use, agricultural, livestock and forestry. Soil degradation caused by compression can often be irreversible is a global problem that is getting worse year after year, because the machines are showing an increase of its mass, but often have no proportional increase in the area of tire-soil contact. This study was conducted to evaluate the physical properties (density, porosity and air permeability), water (water permeability and soil water retention curve) and mechanical (compressibility, in situ stress measures) of three soils (Oxisols, Alfisols 1, and Alfisols 2): Oxisols with crops under no-tillage (NT) and native forest (NF), and Alfisols 1 and Alfisols 2 with crops under no-tillage (NT) and grassland (NG). The different times of loading (7.200 and 600 s) did not affect the preconsolidation pressure (σp) value in three soil layers (0.00-0.07, 0.10-0.15, 0.25-0.30, and 0.40-0.45 m). The σp in Oxisols and Alfisols was greater in the no-tillage soil, compared with the native forest and grassland in the layers of 0.00-0.07, 0.10-0.15 and 0.25-0.30 m, due to the traffic of agricultural machines. Thus, successive farm machinery traffic on no-tillage soil affects σp to deeper soil layers. In theory, such effect was expected in depth Oxisols, since soils with higher clay content pressure is transmitted to greater depths, thereby increasing the depth of compaction. The soil air permeability (ka) and saturated hydraulic conductivity (ks) were higher in Oxisols under native forest, with the largest macroporosity, especially in the uppermost soil layer, where soil drying had no effect on ka. The ks for Oxisols under NF was 754 mm h-1, which is the largest, whereas the smallest was 3 mm h-1 in the surface layer of NT. Measurements of pressure were made in situ with Soil Stress Transducer, SST. When traffic was conducted with the harvester, the highest pressures were measured in the layer 0.00-0.07 m of the Oxisols, and pressure was lower in the layer 0.40-0.45 m of the Ultisol 1, as expected, because in sandy soils the pressures are not transmitted to greater depths. These results show that the no-tillage of the soil can be affected significantly by soil compaction and that appropriate management systems should be used to maintain a balance of physical properties and flow of water and air in the soil.